Slides with English text that are explained in Persian - Monajemi , Alireza; Yaghmaei, Minoo (Student Research in Translational Medicine, 2021)
The common pattern of presentation in the Iranian medical community is lengthy English text in slides that are presented orally in Farsi, both in conferences and classrooms. In this paper, we aim to further explore this phenomenon based on a theory in the domain of cognitive science named the cognitive load theory (CLT). According to Atkinson and Shiffrin's model introduced in 1968, human memory consists of three parts: sensory memory, working memory, and long-term memory. Information first enters the sensory memory, and if received adequate attention and reaches the level of consciousness, it enters the working memory, which, unlike the other two memories, i.e, sensory and long-term memory, has a limited capacity (1). Interestingly, working memory has two separate and independent channels for processing visual and auditory information with a limited and predetermined capacity (dual-channel theory). As a result, the speed of learning in humans restricts (2). In 1988, Sweller proposed a theory of learning called the CLT, in which the three key components of the cognitive structure, i.e. memory systems, learning processes, and types of the cognitive load imposed on the working memory, were merged. According to this theory, because of the limited capacity of the working memory, any factor that imposes an excessive load on this memory will disrupt the learning process (2). Here three types of loads are introduced: 1. Intrinsic load is related to the task. The more complex the information that must be processed by the working memory, the greater the load imposes. – Cont.